PENGARUH BRAND IMAGE, LITERASI KEUANGAN SYARIAH, DAN SHARIAH GOVERNANCE, TERHADAP KEPUTUSAN MENGGUNAKAN JASA PERBANKAN SYARIAH - Niswatun, N; Susilo, Edi (Institut Islam Mamba'ul 'Ulum Surakarta, 2022)
This study aims to analyze the effect of brand image, sharia financial literacy, and shariah governance, on the decision to use sharia banking services in Jepara Regency. This study is a quantitative study, with multiple linear regression analysis method, using SPSS version 16. The results showed that the brand image variable (X1) and Islamic financial literacy variable (X2), significantly influenced the decision to use Islamic banking services in Jepara Regency ( Y). While the shariah governance variable (X3) has no significant effect on the decision to use sharia banking services in Jepara Regency (Y). Simultaneously, the brand image variable (X1), the Islamic financial literacy variable (X2), and the sharia governance variable (X3), have a significant effect on the decision to use Islamic banking services in Jepara Regency.